An Integrated Web-Based GIS Platform for the Environmental Monitoring of Industrial Emissions: Preliminary Results of the Project - Giglione, Giada; Annibaldi, Anna; Iaccarino, Antonio; Capancioni, Roberto; Borghini, Giorgio; Ciabattoni, Fiorenzo; Illuminati, Silvia; Pace, Giandomenico; Memmola, Francesco; Giantomassi, Gianni (Applied sciences, 2022)
The European regulatory framework requires prior authorization for the use of plants and activities that may impact the environment, to ensure an adequate level of environmental and human health protection. Data on industrial wastewater, urban sewage, atmospheric emissions and waste management of installations subject to licenses generate interest among stakeholders (Environmental Protection Agencies, Police Forces, regions, provinces, municipalities, Local Health Authorities, operators, research bodies, citizens), but unfortunately, they are not properly digitized and processed, as they are often unavailable. Therefore, the main goal of this project is to provide a flexible, interactive and easy-to-use tool for stakeholders to allow them to consult these kinds of environmental data. For this purpose, a database integrated with a web-based Geographical Information System (GIS) platform to collect, manage and share pollutant emissions data, is currently being designed and developed. The web platform offers to users interconnected informative modules on required authorizations, license processes and analytical controls. Moreover, stored data from industries and on emissions are georeferenced and displayed in a web GIS map. Stakeholders have free but limited access to specific sections of the web platform, depending on their tasks. They can consult environmental data and GIS representations, download reports or documents and enter new data. This web application seeks to: (1) promote collaboration among stakeholders, (2) simplify the monitoring of an installation’s authorization status and industrial emissions trends, (3) optimize the environmental licensing procedures, (4) enhance the management of environmental control by the relevant authorities, (5) support health and environmental research, and (6) provide industries with innovative services for data transmission. To evaluate the performance and benefits of the newly-developed tool, a real-life pilot case has been applied using data from industries located in the Province of Ascoli Piceno (Marche region, Italy).